Kesesuaian Isi Buku Ajar BIPA â€œSahabatku Indonesiaâ€ untuk Penutur Bahasa Inggris Level 1 (Conformity of BIPA Textbook Contents â€œSahabatku Indonesiaâ€ for Level 1 English Speakers) - Kurniawan Kurniawan; Royan Nur Fahmi; Indrya Mulyaningsih (Indonesian Language Education and Literature, 2022)
Through the Indonesian Language for Foreign Speakers (BIPA) program, various people in the world are interested in learning Indonesian. This study aims to describe the suitability of the BIPA textbook entitled "Friends of Indonesia" to the achievement of learning objectives according to the specified Graduate Competency Standards (SKL). The method used in this research is the qualitative method. This research was conducted in three research steps, namely (1) providing or collecting data, (2) classifying and analyzing data, and (3) presenting the results of data analysis. BIPA teaching materials are devoted to the beginner/basic level (beginner). The results of the study indicate that the book needs to be re-examined regarding the material of the form and meaning of affixes, cultural aspects, and grammatical explanations. Cultural aspects need to be highlighted because language learning is basically a means of diplomacy for the Indonesian people.Melalui program Bahasa Indonesia bagi Penutur Asing (BIPA), berbagai masyarakat di dunia mulai berminat dan mempelajari bahasa Indonesia. Penelitian ini bertujuan untuk mendeskripsikan kesesuaian buku ajar BIPA berjudul â€œSahabatku Indonesiaâ€ terhadap ketercapaian tujuan pembelajaran sesuai Standar Kompetensi Lulusan (SKL) yang ditetapkan. Metode yang digunakan dalam penelitian ini adalah metode kualitatif. Penelitian ini dilakukan dalam tiga langkah penelitian, yaitu (1) penyediaan atau pengumpulan data, (2) pengklasifikasian dan penganalisisan data, dan (3) penyajian hasil analisis data. bahan ajar BIPA yang dikhususkan untuk tingkat pemula/dasar (beginner). Hasil penelitian menunjukkan bahwa buku perlu dikaji ulang terkait: materi bentuk dan makna imbuhan, aspek kebudayaan, dan penjelasan tata bahasa.Â Aspek budaya perlu ditonjolkan karena pembelajaran BIPA pada dasarnya adalah sarana diplomasi bagi bangsa Indonesia.